2019
DOI: 10.1177/1941738119845671
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Lyme Arthritis in the Orthopaedic Patient

Abstract: Context: Lyme disease is the most common tick-borne illness in North America and Europe, and Lyme arthritis is a frequent late-stage manifestation in the United States. However, Lyme arthritis has rarely been reported as a postoperative complication. Evidence Acquisition: The PubMed database was queried through June 2018, and restricted to the English language, in search of relevant articles. Study Design: Clinical review. Level of Evidence: Level 3. Results: A total of 5 cases of Lyme arthritis as a postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…[2][3][4] Based on the limited available literature, the ideal treatment of postoperative Lyme infection, specifically a Lyme PJI, is still unclear. 18,19 Wright and Oliverio reported successful treatment with the utilization of only antibiotics. 1 Adrados et al, Collins et al, and Ali et al reported a combined total of 4 cases treated successfully with surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Based on the limited available literature, the ideal treatment of postoperative Lyme infection, specifically a Lyme PJI, is still unclear. 18,19 Wright and Oliverio reported successful treatment with the utilization of only antibiotics. 1 Adrados et al, Collins et al, and Ali et al reported a combined total of 4 cases treated successfully with surgical intervention.…”
Section: Discussionmentioning
confidence: 99%